Psychometric Properties of the BIS/BAS Scales and the SPSRQ in Flemish Adolescents - Vandeweghe, Laura (Psychol Belg, 2016)
OBJECTIVE: Gray’s Reinforcement Sensitivity Theory (RST) is a frequently used model of personality that is relevant to the period of adolescence. However, the psychometric properties of the most frequently used questionnaires to measure the RST-constructs, namely the Behavioural Inhibition System and Behavioural Activation System Scales (BIS/BAS Scales) and the Sensitivity to Punishment and Sensitivity to Reward Questionnaire (SPSRQ), are rarely examined in samples of adolescents. Therefore, the goal of the present study was to examine the two-factor structure, reliability and convergent validity of the BIS/BAS Scales and SPSRQ in a Flemish adolescent community sample. METHOD: A sample of 579 adolescents (39.5% boys; 14–19 years) was recruited. The proposed two-factor structure was assessed using Exploratory Structural Equation Modeling. Reliability was evaluated using internal consistency and construct validity was examined with the correlations between the two questionnaires and with the Temperament and Character Inventory–short form (TCI-SF). RESULTS: After the removal of problematic items, and the addition of correlated errors, all indices indicated a good fit for the two-factor structure of the modified BIS/BAS Scales. For the modified SPSRQ, three fit indices indicated a good model fit, while a fourth fit index was slightly below the cut-off score of an adequate model fit. Internal consistency of both questionnaires was sufficient. In general, the associations with scales of the TCI-SF were as expected, with positive correlations between BIS-related scales, and between BAS-related scales of all three instruments. DISCUSSION: In Flemish adolescents, the use of a two-factor model to analyze data gathered with the modified BIS/BAS Scales or modified SPSRQ seems appropriate.